CIVIL LIABILITY OF REAL ESTATE NOTARY IN JORDANIAN LEGISLATIONS: A COMPARATIVES STUDY - Jameel, Thamer Aref; Al-byat, Mohammed Hatem (Journal of Economic, Administrative and Legal Sciences, 2021)
The notary has enjoyed a privileged position in the legal system, and the work of the notary is considered a form of achieving justice, as this profession has an impact on society, as it is considered one of the most dangerous professions because the nature of the documentary’s work is based on establishing the rights of individuals in an official form such as the transfer of ownership, and given the importance of the documentary in The law has assigned the legislator a special protection for it and in return impose a penalty for everyone who prejudices the sanctity of the contracts notarized and concluded by the real estate notary, as the authority of the notary is considered the authority of the law, as the notary is authorized by the state and has rights and obligations regulated by law. Documentation has also become one of the basic factors in the lives of individuals and their relationships in society, as it has become a tool in the hands of the state to follow up and supervise legal work, and with the development of the notary’s work with social and economic openness, there has become a great demand for documentation by individuals in order to ensure their rights and obligations. It is considered a legal guarantee of individual rights (Makhlouf, 2015, p. 81). We conclude from this study that the notary is responsible for his professional mistakes towards his client, and for this reason the aggrieved (client) has the right to refer to the notary or the authority to which the notary is affiliated in his work based on the provisions of the responsibility of the follower for the fault of the follower, and the aggrieved party has the right to sue them together, as the aim of these The study is a statement of the civil liability that falls on the real estate notary and a statement of the duties and rights that he owes. As for the lawsuit for compensation for the damage that the client suffered against the notary, the law did not distinguish it with special provisions in terms of its prescription period, but rather subjected it to general provisions in the civil law, In order for the civil notary to be responsible, the general elements of any liability must be met, which are three pillars: First, the documentary error, whether intentional or not, and it occurred before the writing of the notary, or during its writing, or after the writing of that contract, and the criterion by which this error is measured is the behavior of the notary Average in terms of adequacy, and that the damage is realized and is a direct result of that error.